Predictive Value of Tumor Size on The Incidence of Peritumoral Edema on Pre-Surgery Head Mri of Meningioma Patients - Pangestu, Rahmawati Dianing; Faisal, Arif; Utomo, Bambang Purwanto (Rumah Sakit Akademik Universitas Gadjah Mada, 2024)
Background : Peritumoral brain edema (PTBE) of meningioma causes morbidity, poor clinical outcomes and complicates surgery. Tumor size correlates with the incidence of PTBE. However, the threshold value for tumor size that cause PTBE in meningioma has not been widely studied. Objective: To determine the threshold value for meningioma size that can predict the incidence of peritumoral edema in general and based on specific intracranial locations on pre-operative head MRI.Methods: This is a cross sectional study on patients with intracranial meningioma who had undergone head MRI imaging at Dr.Sardjito Hospital in the period of 2018-2022 retrospectively. An analysis was carried out to find the threshold value for meningioma size and the prevalence ratio to predict the incidence of PTBE. Results: The cut-off volume for intracranial meningioma was >44 cm3 with RP of 3.61 (p=0.01) in general. Simultaneously, large tumor volume (≥44 cm3) has the strongest correlation to the incidence of peritumoral edema (p=0.01). The cut-off volume for meningioma in supratentorial non-skull base was >22 cm3 with RP of 2.54, while in supratentorial skull base was >54 cm3 with RP of 23.33 (p=0.01). The cut off volume for meningioma in infratentorial region was >19.75 cm3 with RP 3.0 (p=0.52). Conclusion: The cut-off value for intracranial meningioma volume to predict the incidence of peritumoral edema is 44 cm3. There are differences in the cut-off values of meningioma volume and prevalence ratios based on specific intracranial locations to predict the incidence of PTBE in meningioma.